PENGENDALIAN SISA MATERIAL KONSTRUKSI PADA PEMBANGUNAN RUMAH TINGGAL - Asnuddin, Andi (MEKTEK, 2010)
Waste material controlling in home building is very advantage involving, (1) tightening of contruction fee,(2) finishing process and job easily, (3) supporting of building environmental friendly.Factors which become consideration to control waste material on home building are (1) planning of designof site and ground plan, (2) material allocation, (3) using kinds of material, (4) keeping place and (5) abilityof employers.In general, kinds of waste material which are taken in home building are (1) ceramics pieces, (2) waste woodfrom scaffolding and mould of concrete (sloof, column, beam), (3) iron pieces, and (4) bricks pieces.Waste material can not be controlled if it uses kind of materials which can not be ordered in few contentsuitable with need because it is related to container and low limitation order